2011
DOI: 10.1021/ie102566y
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Graphene on Antidripping and Fire Resistance of Intumescent Flame Retardant Poly(butylene succinate) Composites

Abstract: Intumescent flame retardant poly(butylene succinate) (IFRPBS) composites with enhanced fire resistance were prepared using graphene as synergist. The morphology of fracture surfaces of the composites was investigated by scanning electron microscopy (SEM). The limiting oxygen index (LOI) values increased from 23.0 for the pure PBS to 31.0 for IFRPBS with 20 wt % IFR loading. The addition of graphene further improved the LOI values of the composites and exhibited excellent antidripping properties. The UL-94 V0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
138
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(148 citation statements)
references
References 30 publications
5
138
0
Order By: Relevance
“…To solve the abovementioned problems, many researchers have made significant efforts to use graphene as an adjuvant in combination with other conventional flame retardants such as intumescent flame retardants and aluminium hydroxide [46][47][48][49][50][51], melamine polyphosphate [52], carbon black [53], layered double hydroxides (LDHs) [54], brominated polystyrene and antimony trioxide (Sb 2 O 3 ) [55], and aluminium hypophosphite [56]. As shown in Fig.…”
Section: Conventional Flame Retardants-graphene Blending Flame Retardantmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the abovementioned problems, many researchers have made significant efforts to use graphene as an adjuvant in combination with other conventional flame retardants such as intumescent flame retardants and aluminium hydroxide [46][47][48][49][50][51], melamine polyphosphate [52], carbon black [53], layered double hydroxides (LDHs) [54], brominated polystyrene and antimony trioxide (Sb 2 O 3 ) [55], and aluminium hypophosphite [56]. As shown in Fig.…”
Section: Conventional Flame Retardants-graphene Blending Flame Retardantmentioning
confidence: 99%
“…The reason lies in that rGO is well dispersed with little agglomeration (Fig. 5a) and exfoliated in the IFRPU composites, thereby preventing the migration and increasing the dispersion of the intumescent [49] used graphene as a synergist to enhance the fire resistance of intumescent flame retardant poy(butylene succinate) (IFRPBS). They found that adding 2 % graphene to IFRPBS with 18 % IFR further increases LOI to 33 (adding 20 % IFR alone gives an LOI of 30).…”
Section: Conventional Flame Retardants-graphene Blending Flame Retardantmentioning
confidence: 99%
“…In addition, there are some other reports regarding the application of graphene as a flame retardant additive in polymer composites. [10][11][12][13] However, bare graphene was used as a flame retardant in previous reports, such that a high loading is required to achieve a good flame retardant effect. Therefore, the use of graphene alone as the flame retardant still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphinate salts possessing the properties such as high flame retardancy, anti-dripping during combustion and good compatibility with matrix are therefore highly desired [21][22][23][24]. In addition, a highly efficient flame retardant should show a decomposition temperature similar to that of the polymer.…”
Section: Introductionmentioning
confidence: 99%